Dietary carotenoids predict plumage coloration in wild house finches. - Hill, Geoffrey E (2002)
Carotenoid pigments are a widespread source of ornamental coloration in vertebrates and expression of carotenoid-based colour displays has been shown to serve as an important criterion in female mate choice in birds and fishes. Unlike other integumentary pigments, carotenoids cannot be synthesized; they must be ingested. Carotenoid-based coloration is condition-dependent and has been shown to be affected by both parasites and nutritional condition. A controversial hypothesis is that the expression of carotenoid-based coloration in wild vertebrates is also affected by the amount and types of carotenoid pigments that are ingested. We tested this carotenoid-limitation hypothesis by sampling the gut contents of moulting house finches and comparing the concentration of carotenoid pigments in their gut contents with the colour of growing feathers. We found a positive association: males that ingested food with a higher concentration of carotenoid pigments grew brighter ornamental plumage. We also compared the concentration of carotenoids in the gut contents of males from two subspecies of house finches with small and large patches of carotenoid-based coloration. Consistent with the hypothesis that carotenoid access drives the evolution of carotenoid-based colour displays, males from the population with limited ornamentation had much lower concentrations of carotenoids in their gut contents than males from the population with extensive ornamentation. These observations support the idea that carotenoid intake plays a part in determining the plumage brightness of male house finches.